The Role Of Financial Management and Digital Marketing In Efforts To Increase Sales Turnover For MSMEs In Traditional Markets - Arif Budiarto; Norvadewi; Sunyoto; Ratih Pratiwi; Retno Kusumaningrum (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
Changes in the shopping behavior of the Indonesian population from 2011 to the present have resulted in the market in Indonesia proliferating. Consumers like online shopping because it tends to be more practical and modern and can be done anytime without leaving the house when they need the items they want. This research is qualitative research with a descriptive analysis model with library study where this research attempts to provide an overview of phenomena or events that are currently occurring, which are now taking place. Financial Management influences Micro, Small and Medium Enterprises. Micro, Small, and Medium Enterprises (MSMEs) financial management has a significant influence. The use of digital marketing creates opportunities for Traditional Market MSMEs to develop their businesses and be able to become an economic force in the current era of digitalization. Policies that support transparency and Sharia business ethics can increase consumer trust and facilitate digital interactions between Sharia MSMEs and their consumers. Further analysis shows that government policies supporting the development of Sharia economics can help Sharia MSMEs in traditional markets adopt better financial management and digital marketing practices.